O uso e a percepção ambiental de áreas úmidas por uma população ribeirinha na região da Bacia Hidrográfica do Rio Taquari-Antas, Rio Grande do Sul - Baptista, Cristina Paes Barreto (Universidade do Vale do Rio do Sinos, 2007)
Wetlands are important ecosystems for biodiversity protection; they show a great wealth of species and high levels of endemism. These environments are sources of natural resources for human populations, and they are among the most productive ecosystems in the world. Impacts on wetlands include both some habitat changes and destruction. Mankind depends on the sustained usage of wetlands. Ethnobiology studies the body of knowledge human populations have about the natural resources, the taxonomies, the classifications and the ecosystems on which they depend for their trade or subsistence. To acknowledge the native populations as part of the ecosystem is essential for biodiversity preservation. The ecosystem is directly and indirectly influenced by the relationships the human populations keep with hydrological resources. This being said and upon recognizing the significance of wetlands preservation, besides admitting (acknowledging) the great interaction and body of knowledge traditional populations have about th
Usage and Environment Perception of Wetlands by a River Population in the River Basin of the Taquari-Antas Region, Rio Grande do Sul
Keywords: estratégias de sobrevivência; percepção ambiental; recursos pesqueiros; ribeirinhos; rios; sustentabilidade; áreas úmidas; environment perception; fishing resource; river dwellers; rivers; survival strategy; sustentability; wetlands; Ciências Biológicas